Use of video games in industry and education - Quintana-Cruz, Hernan (2022)
Video games are digital products used in different contexts, not necessarily in those of play, because they have characteristics that allow the improvement of many of the videogamers’ skills. This article reviews the trends in the use of video games in industrial and in educational contexts. It also presents some definitions of necessary concepts that will provide us with a better understanding of these digital products. It concludes that video games are important tools due to their ability to generate motivation and engagement, so their application in contexts other than entertainment would be beneficial.